GAMBARAN DUKUNGAN KELUARGA DALAM UPAYA PENCEGAHAN DEPRESI PADA LANSIA DI PUSKESMAS BATUA RAYA MAKASSAR - Syahrir; Nurul Fuady Fitryani Ahmad (Stikes Graha Edukasi Makassar, 2022)
Family support is a social resource that can assist individuals in dealing with a stressful event. The purpose of this study was to find out the description of family support in efforts to prevent depression in the elderly at the Batua Health Center in Makassar. This research method is descriptive, with cross sectional method. The population in this study were all families and the elderly at the Batua Raya Makassar Health Center, namely 53. The sample taken was 39 respondents, which were obtained using the Slovin formula. The results obtained from the data analysis test showed that there was a picture of good emotional support for 31 respondents (79.5%), good appreciation support for 25 respondents (75.8%), good information support for 30 respondents (76.9%) ), and prevention of depression in the elderly is good, namely 34 respondents (87.9%). The conclusion shows that most of the elderly have good depression prevention supported by good family support. It is hoped that it will provide more support to the elderly so that the elderly do not experience excessive depression which will lead to health problems for the elderly